Estimates of Parental Best Linear Unbiased Predicted (BLUP) Additive Genetic Values for Oil Yield in an Indonesian Oil Palm Breeding Programme - A. R. Purba; A. Flori; L. Baudouin; P. Amblard; S. Hamon (Zuriat, 2004)
The additive genetic value for oil yield of 135 parents from several African populations tested in the first cycle of Indonesian Oil Palm Research Institute (IOPRI) breeding programme were estimated by best linear unbiased prediction (BLUP) using an unbalanced data set. These values were used to evaluate the possibility of reduction in generation selection time in an oil palm breeding programme. The ranks of parental additive genetic values obtained with early yield period and whole cycle was found to be consistent. These make that highly potential parents could be selected and recombined at a more precocious time in order to reduce the period between cycle. Since oil yield trait is mainly controlled under additive gene effect, the recombination should be done carefully for retaining as highly as possible this character in a parent to be improved.